The Relationship between Classical Fiqh and Modern Social Needs in the Formation of Islamic Law - Samsidar Samsidar (PT. Anagata Sembagi Education, 2025)
This article examines the relationship between classical fiqh and modern social needs in the formation of Islamic law, focusing on the normative and methodological tensions arising from contemporary legal development. Classical fiqh, rooted in structured juristic reasoning and historical context, is often perceived as rigid when confronted with rapid social transformation, technological advancement, and institutional complexity. This study identifies three principal legal issues: the mischaracterization of classical fiqh as a static normative product, methodological stagnation resulting from restricted conceptions of ijtihād, and the absence of a coherent framework for integrating social change into Islamic legal formation. Employing a normative juridical method with conceptual, statute, and case approaches, the article analyzes contemporary Islamic legal discourse, fatwa practices, and adaptive jurisprudence across various legal fields. The analysis demonstrates that classical fiqh inherently possesses adaptive capacity through its methodological tools, including maqāṣid al-sharīʿah, qawāʿid al-fiqhiyyah, and juristic pluralism. This article argues that the perceived conflict between tradition and modernity stems not from doctrinal incompatibility but from methodological misapplication. It proposes a prescriptive integration framework that institutionalizes continuous ijtihād, strengthens maqāṣid-based reasoning, and revitalizes methodological pluralism to ensure that Islamic law remains doctrinally authentic, socially responsive, and normatively coherent in contemporary contexts.